Surgical technology, Anaesthesia and pain medicine, ambulatory anaesthesia for outpatient surgery - Fiona, Agbor Tabe (Jour Med Resh and Health Sci, 2020)
Owing to burgeoning improvements in surgical technology, anaesthesia and pain medicine, ambulatory anaesthesia for outpatient surgery has become commonplace, with a proportion of 66% in the United States of America, 50% in the United Kingdom, 11%-23% in India and an ambitious 75% in the next decade. Its advent was driven by financial and economic issues which it adequately abates by 25%-75% lesser than an inpatient procedure. Among other benefits to patients, healthcare providers, insurance companies and hospitals, outpatient anaesthesia decreases costs, minimises respiratory failure, enhances early hospital discharge, contributes to the economic growth of the nation, and decreases exposure to nosocomial infections. The growing complexity of surgical methods and number of comorbidities these days have increased the indications for ambulatory anaesthesia. In order for it to be safe and successful, the appropriate selection of patients, surgical and anaesthetic methods as well as postoperative management should be considered simultaneously. Nevertheless, ambulatory anaesthesia is still hindered by limited resources, inadequate expertise, and poor coordination between medical and organisational aspects of care in some countries. This problem can be minimised by providing resources and the training of healthcare providers on better organisation and the use and manipulation of these equipment through seminars and conferences. Furthermore, the global burden of disease study projects an increase in future anaesthesia demands due to the ever rising disease burden worldwide. This can be resolved by adequately managing the challenges of ambulatory anaesthesia and creating more centers either within or without hospitals. By and large, safe and convenient cost-effective methods to ensure patient's quick return to function and recovery are necessary in ambulatory anaesthesia. Still and all, many challenges are being confronted daily, and numerous barriers have to be broken before ambulatory anaesthesia and surgery can make its concrete place and establishment in the clinical society.